PEMBUATAN ARANG AKTIF DARI TEMPURUNG KELAPA DAN KAYU BAKAU DENGAN CARA AKTIVASI UAP - Hartoyo NurmaJa Hudaya (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Experimental study Q.n steam activation of biomaas char for manufacturing activated charcoal wa conducted in Forest Product Reaearch and Development Centre, Bogor. The material used in these experiment were coconut shell and mangrove wood. This study was intended to investigate the effect of temperature and reaction time on the activated carbon yield and quality.Treatment temperature given for adivation were three levels being 600, 700, 900°, with resvective reaction time 10, 2O, 30, 40, 50 minutes.steam flow rate was made constant at 0.5 kg/hr. the result showed that some of these Conditions could produce good quality activated carbon as determined by iodine index and phenol lndex. This quality is within the commercial standard made by the American Water Works Association (AWWA) and the Indonesian Industrial Standard.The optimum processing condition for manufacturing coconut shell activated Charcoal was at 900° C activation tem perature and 40 minute of reaction time, and yield of 57.0% with the iodine number of 780,9 mg/g. The optimum condition for producing activated charcoal from bakau (Mangrove) was at 700° C within 40 minute. The yield was 78.0% and the iodine number of 689.9 mg/g or 69.0%.A compariaon of rasults with the surveyed data shows that the qualities of the activated charcoal obtained from the experiment is comparable with the activated carbon from the commercial brand.